The Role of Promotion in Determining the Effect of Price and Location on the Decision to Purchase Subsidized Housing - Yusup Supriadi; Liza Nora (Transpublika Publisher, 2026)
Backgrounds: The increasing competition in the housing property sector requires developers to understand key factors influencing consumers’ purchasing decisions. Price and location are commonly considered primary determinants, while promotional strategies may strengthen consumers’ decision-making processes in selecting residential properties. Objectives: The study aims to investigate the effects of Price and Location on Purchase Decisions by embedding Promotion as a moderating construct among consumers of Buana Residence Housing. Methodology: This research adopted a quantitative associative approach. Data collection involved distributing questionnaires to 110 consumers and prospective consumers of Buana Residence Housing, which were analysed using the PLS-SEM method through SmartPLS software. Findings: The structural assessment confirms that Price constitutes a dominant predictor of Purchase Decision (β = 0.446), whereas Location provides an additional contributory influence (β = 0.217). Promotion demonstrates independent explanatory capacity (β = 0.292) and functions as an effect-strengthening mechanism, augmenting the Price-Purchase Decision and Location-Purchase Decision relationships with interaction coefficients of 0.496 and 0.471. Conclusions: The findings suggest that promotion operates as an amplifying contingency through which the explanatory power of price and location becomes more pronounced in shaping consumer purchasing decisions, indicating that integrated pricing, strategic location advantages, and promotional efforts are essential in improving housing purchase decisions. Developers should strengthen their marketing strategies to maximize the influence of price and location on purchasing decisions.